Novel Dynamic S-Box Based on Password Key and Circle Map - Khudhair, Ala'a Talib; Gbashi, Ekhlas Khalaf; Maolood, Abeer Tariq (Iraqi Journal of Science, 2023)
Many cryptosystems and security techniques use substitution boxes to ensure the data’s secure communication. A new technique is presented for generating a robust S-box to fulfill security requirements. The AES algorithm represents a block cipher cryptographic algorithm. It was selected by the National Institute of Science and Technology as the optimal cryptographic algorithm in 2011. Through the study of the properties of original S-BOX, this algorithm has been subjected to a number of attacks (linear, differential, statistical, and interpolation), and original S-BOX has been static, which makes the attack strong and shows a weakness in the algorithm.  It is necessary to make this algorithm more efficient and powerful through the improvement of the dynamic generation of the steps for the protection of textual data security. This paper proposes a dynamic S-Box based on the user's password key (8 chars), shifting, and a 1D circle map. The results in this work indicated that the suggested approach presents a secure S-BOX, which is considered to have 255 differences identified when 1 bit of the key is changed; therefore, about 99% of the S-Box has been changed. Also, an inverse table of S-Box (16*16) is generated via the S-Box output created from the above-mentioned suggestions for returning the values regarding the union of the column and the row for all the S-Box generated values. We examine the quality of our S-Box through various well-known performance parameters. All of the analysis yields very encouraging results, certifying that the generated S-box meets all criteria that are required for reliable and secure encryption. Just a few milliseconds are needed to implement it.